2002
DOI: 10.1093/jn/132.11.3482s
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Effects Relevant to Cancer

Abstract: Flavonoids, such as daidzein and genistein, present in dietary plants like soybean, have unique chemical properties with biological activity relevant to cancer. Many flavonoids and polyphenols, including resveratrol in red wine and epigallocatechin gallate in green tea, are known antioxidants. Some of these compounds have estrogenic (and antiestrogenic) activity and are commonly referred to as phytoestrogens. A yeast-based estrogen receptor (ER) reporter assay has been used to measure the ability of flavonoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 98 publications
1
56
1
4
Order By: Relevance
“…Genistein has a wide range of biological actions that suggest it may be of use in cancer treatment. Its molecular actions include: an inhibitory effect on protein tyrosine kinases, DNA topoisomerase Ⅰ and Ⅱ, and ribosomal S6 kinase; antiestrogenicity; antioxidant activity; anti-angiogenesis activity; suppression of cell proliferation; induction of differentiation and modulation of apoptosis [13][14][15] . However, few data are available on the effects of genistein on metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein has a wide range of biological actions that suggest it may be of use in cancer treatment. Its molecular actions include: an inhibitory effect on protein tyrosine kinases, DNA topoisomerase Ⅰ and Ⅱ, and ribosomal S6 kinase; antiestrogenicity; antioxidant activity; anti-angiogenesis activity; suppression of cell proliferation; induction of differentiation and modulation of apoptosis [13][14][15] . However, few data are available on the effects of genistein on metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations more physiologically achievable in the plasma (from 0.1 µM to 10 µM) after the consumption of meals rich in flavonoids (Manach et al, 2004), these compounds are thought to protect against degenerative diseases (i.e., E2-related cancers) by regulating ER activity (Birt et al, 2001;Brownson et al, 2002;Totta et al, 2004). This has allowed us to enter a new era of understanding the mechanisms by which flavonoids exert their effects on human health.…”
Section: Conclusion Conclusion Conclusion Conclusion Conclusionmentioning
confidence: 99%
“…On the contrary, Asian women (large isoflanoids consumers) and vegetarians have a lower than average breast cancer risk (Limer and Speirs, 2004). In addition, flavonoids have been shown to induce responses consistent with the protective effects of fruit and vegetable rich diets against cancer in both in vitro test systems and small animal models (Hollman et al, 1996;Gamet-Payrastre et al, 1999;Birt et al, 2001;Brownson et al, 2002;KeinanBoker et al, 2004). The anticancer effect of nutritional flavonoids could represent other anti-estrogenic effects ascribed to these compounds.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…For instance, resveratrol-induced apoptosis has repeatedly been reported to be accompanied by increased caspase activity (Ferry et al, 2002;Kim et al, 2004;Wolter et al, 2001). In addition, resveratrol-induced apoptosis was shown to be associated with Bax mitochondrial translocation (Mahyar-Roemer et al, 2002), inhibition of AKT activity (Brownson et al, 2002), up-regulation of the oncogene suppressor p53 (Narayanan et al, 2003), and down-regulation of cyclin D1 (Joe et al, 2002). In other studies, resveratrol has been shown to act via c-Jun NH 2 -terminal kinase (JNK), as resveratrol-induced p53-dependent transcriptional activity and apoptosis were blocked upon expression of a dominant-negative mutant of JNK or upon disruption of JNK1 or JNK2.…”
Section: Introductionmentioning
confidence: 99%